DEVELOPING MEDIA BASED ON POWTOON IN TEACHING WRITING RECOUNT TEXT FOR GRADE VIII STUDENTS IN SMP MUHAMMADIYAH 1 MEDAN - Maryam Nerissa; Anni Holila Pulungan; Yeni Erlita (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2020)
The study was aimed to develop media based on PowToon in teaching writing recount text for grade VIII students in SMP Muhammadiyah 1 Medan. This study was conducted by using Research and Development (R & D) design through six stages; gathering information and data, analyzing data, designing materials, validating by experts, revising, and final product. The subject of the study was Grade VIII of SMP Muhammadiyah 1 Medan. The data were gathered by administering interview to English teacher and distributing questionnaire to 30 respondents to get the students’ needs. The interview and questionnaire result prove that the students’ needs English learning media which can motivate the students to understand about the recount writing. The product has been validated by experts. The result of the product was videos that contain audio-visual media to be used in mastering the recount text writing. The result of experts’ validation showed that the media was an appropriate media to be used in teaching writing recount text by getting the average percentage of 95% categorized as excellent.Keywords: PowToon, Recount Text, Research and Development (R&D)